Meningkatkan Kinerja SDM Dalam Kunjungan Pada Toko Butik Fourteen - Indah Dahlia; Santi Pertiwi Hari Sandi; Dwi Epty Hidayati (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This article examines the challenges faced in improving Human Resources (HR) performance in the context of visiting a boutique store. A visit to a boutique store is an important aspect in influencing customer satisfaction and achieving business goals. However, to achieve optimal results, qualified and competent human resources are needed in serving customers. The main challenges faced in improving HR performance during visits to boutique stores include improving employee skills, communication skills with customers, the ability to provide advice and reccomendations to customer, and the ability to maintain good relationships with customers. In addition, there are also challenges in managing time, dealing with dissatisfied customers, and maintaining consistency in servise.